2017
DOI: 10.5301/ijbm.5000280
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of IL-4R Enhances Proliferation and Invasion of Hepatocellular Carcinoma Cells

Abstract: IL-4R plays an important role in regulating HCC cell survival and metastasis, and regulates the activity of the JAK1/STAT6 and JNK/ERK1/2 signaling pathways. We therefore suggest that IL-4/IL-4R may be a new therapeutic target for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…They designed the IL4-Pseudomonas exotoxin (IL4-PE) conjugate and the treatment of IL4-PE decreased the colony formation ability of thyroid cancer cells and tumor growth in thyroid xenograft tumor model [64]. Furthermore, IL4R plays an essential role in regulating hepatocellular carcinoma (HCC) cell survival, proliferation, and metastasis and regulates the activation of JAK1/STAT6 and Jnk/Erk1/2 pathways [65]. As shown in the Figure 2G, interestingly, the knockdown of the IL4R complex component caused the downregulation of each other.…”
Section: Discussionmentioning
confidence: 99%
“…They designed the IL4-Pseudomonas exotoxin (IL4-PE) conjugate and the treatment of IL4-PE decreased the colony formation ability of thyroid cancer cells and tumor growth in thyroid xenograft tumor model [64]. Furthermore, IL4R plays an essential role in regulating hepatocellular carcinoma (HCC) cell survival, proliferation, and metastasis and regulates the activation of JAK1/STAT6 and Jnk/Erk1/2 pathways [65]. As shown in the Figure 2G, interestingly, the knockdown of the IL4R complex component caused the downregulation of each other.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that downregulation of IL-4/IL-13 receptors showed suppression of tumor activity in other cancers. Guo et al showed that downregulation of IL-4R led to enhanced apoptosis, diminished proliferation, and reduced invasion of hepatocellular carcinoma cells, and abolished IL-4-induced activation of JAK/STAT6 and JNK/ERK1/2 signaling pathways [ 129 ]. Venmar and colleagues reported that IL-4Rα-downregulation decreased metastatic capacity in breast cancer [ 62 ].…”
Section: Future Directions Of Researchmentioning
confidence: 99%
“…Elevated plasma level of IL-4 was revealed in liver cancer (Talaat et al, 2016). Interestingly, it has been reported that IL-4 induces the activation of the JNK/extracellular signal-regulated kinase (ERK)1/2 pathway to promote the tumorigenesis of HCC (C. Guo et al, 2017).…”
Section: Cell Ell B Biology Iology I International Nternationalmentioning
confidence: 99%
“…Elevated plasma level of IL‐4 was revealed in liver cancer (Talaat et al, 2016). Interestingly, it has been reported that IL‐4 induces the activation of the JNK/extracellular signal‐regulated kinase (ERK)1/2 pathway to promote the tumorigenesis of HCC (C. Guo et al, 2017). Notably, the ERK pathway displayed hyper‐activation in HCC, mediated the cell growth, and shared correlation with the drug resistance (Nwosu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%